The Relationship between Science Learning Skills and Science Literacy Levels of Classroom Teacher Candidates - Uyanık, Gökhan (Journal of Computer and Education Research, 2025)
The science learning skills and science literacy levels of prospective primary school teachers, who are the teachers of the future, are very important. In this respect, this study is considered to be important in terms of determining this situation. Aim of this study is to investigate the relationship between science learning skills and science literacy levels of primary school teacher candidates. Relational survey model was used in this study. The sample of research consisted of 242 teacher candidates. Science learning skills scale and science literacy scale were used as data collection tools. In addition to descriptive statistics, independent t-test and ANOVA analysis were applied to analyze the data. According to findings, it was determined that the science learning skill levels of the classroom teacher candidates were above average. Besides, there was no significant difference between the science learning skill scores of the teacher candidates in terms of gender and grade level variables. When the science learning skill scores and science literacy scores were examined in terms of the grade level and gender variables, it was concluded that there was a significant difference between the scores of the prospective teachers. Besides, science literacy levels of classroom teacher candidates were below average. There was at medium level positive and significant relationship between the science learning skills and science literacy levels of teacher candidates.
Keywords: Sınıf Eğitimi; Classroom teacher candidates; science learning skills; science literacy; Classroom Education